Effects of Occasional and Habitual Wearing of High-Heeled Shoes on Static Balance in Young Women - Yamada-Yanagawa, Ayano; Sasagawa, Shun; Nakazawa, Kimitaka; Ishii, Naokata (Frontiers in Sports and Active Living, 2022)
The purpose of this study was to examine the effects of occasional and habitual wearing of high-heeled shoes on static balance in young women. Groups of habitual high-heel wearers and non-wearers (n = 7 in both groups) were asked to stand quietly on a force platform without shoes (WS condition) or with high heels (heel area 1 cm2, heel height 7 cm) (HH condition). During the trials, the center-of-pressure (CoP) position in the anterior-posterior direction was measured, and its root mean square (as a measure of postural sway magnitude, CoPRMS) and mean velocity (as a measure of regulatory activity, CoPMV) were calculated. To further examine the effect of high-heel wearing on the temporal aspects of slow and fast processes in static balance, the CoP sway was decomposed into low- (below 0.5 Hz) and high- (above 0.5 Hz) frequency components, and then spectral analysis was performed. Results showed that the CoPRMS was not significantly different between the groups or between the shoe conditions, indicating that wearing high heels with a heel height of 7 cm did not increase the magnitude of postural sway, irrespective of high-heel experience. The CoPMV was significantly larger in the HH condition than in the WS condition, whereas it was not significantly different between the groups. This result indicates that wearing high heels increased the amount of regulatory activity in both habitual wearers and non-wearers. The spectral analysis further showed that habitual high-heel wearers showed significantly decreased rate of regulatory activity than non-wearers, both while standing with and without high heels. These results suggest that use-dependent changes in static balance control are evident in both high-heeled and without shoes conditions.